The hope of exponential growth – Systems mapping perspective on birth of platform business - Pussinen, Pasi; Wallin, Arto; Hemilä, Jukka (Digital business (Amsterdam), 2023)
The traditional pipeline-based approach to operating business is currently challenged by the platform-based approach. The research on digital platforms and platform business is well established and includes multiple different design frameworks for building platform business but they seem to lack the dynamic nature of platform design. We explore the birth of digital transaction platforms as a dynamic process to demonstrate the dynamic complexity of designing platform-based businesses. The paper presents a multiple case study focusing on the birth phases of four resource constrained start-ups. Based on literature study and theme interviews, we apply systems mapping to analyse the early growth of four digital platform ecosystems. Our findings indicate that the growth of platform-based business is a result of various self-reinforcing and balancing feedback loops, which create dynamic behaviour of the system. In the early phases of platforms lifecycle, start-ups struggle to offset the dominating feedback structures that limit the growth. These feedback structures vary based on business environment and platform design choices made by the platform company. The research contributes to academic discussion on digital business by providing empirical and theoretical insights into growth dynamics of business based on digital platforms. •Businesses based on digital platforms are associated with rapid growth potential.•The growth of a platform may be very slow in the early phases of the lifecycle.•Careful design of business is needed to harness network effects.•Resources needed for business based on digital platforms are underestimated.